Social and Structural Determinants of Health Inequities in Maternal Health - Crear-Perry, Joia (J Womens Health (Larchmt), 2021)
Since the World Health Organization launched its commission on the social determinants of health (SDOH) over a decade ago, a large body of research has proven that social determinants—defined as the conditions in which people are born, grow, live, work, and age—are significant drivers of disease risk and susceptibility within clinical care and public health systems. Unfortunately, the term has lost meaning within systems of care because of misuse and lack of context. As many disparate health outcomes remain, including higher risk of maternal mortality among Black women, a deeper understanding of the SDOH—and what forces underlie their distribution—is needed. In this article, we will expand our review of social determinants of maternal health to include the terms “structural determinants of health” and “root causes of inequities” as we assess the literature on this topic. We hypothesize that the addition of structural determinants and root causes will identify racism as a cause of inequities in maternal health outcomes, as many of the social and political structures and policies in the United States were born out of racism, classism, and gender oppression. We will conclude with proposed practice and policy solutions to end inequities in maternal health outcomes.